(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The influence of different components on proline oxidaze (PO) and piroline-5-carboxilate dehydrogenaze (P5KD) has been studied. In all stages of metamorphoses of the haricot beetlefly Acantoscelides obtectus Say. NaF considerably depresses PO and P5KD activity. The influence of different concentrations of citrate and adenylic nucleotides on enzymes activity of proline degradation of beetles has been investigated. The high concentrations of the stated compounds depress the activity of enzymes, which are depressed by ATF more than 87% under 10–5M.